Fertility and pregnancy outcomes after transvaginal cervico-isthmic cerclage. (November 2017) - Neveu, Marie-Emmanuelle; Fernandez, Hervé; Deffieux, Xavier; Senat, Marie-Victoire; Houllier, Marie; Capmas, Perrine
Abstract: Introduction: Prematurity is the leading cause of neonatal morbidity and mortality. Cervical insufficiency seems to be the main risk factor. Treatment is cervical cerclage. In case of failure, a cervico-isthmic cerclage by Fernandez' technique, with the placement of a polypropylene sling by vaginal approach during the first trimester of pregnancy, has proven its effectiveness. The aim of our study is to report effectiveness of Fernandez' cervico-isthmic cerclage in subsequent pregnancies. Materials and methods: This retrospective study, was conducted from March 2002 to April 2014 in the gynecologic department of two teaching hospitals. The inclusion criterion was history of cervico-isthmic cerclage using Fernandez's technique during the previous pregnancy. This study received IRB approval numberCEROG 2016-GYN-0302 . Results: 125 women underwent a definitive cervico-isthmic cerclage. The total percentage of neonatal survival after 14 weeks was 91% and the total percentage of neonatal survival after 24 weeks of gestation was 98.2%. Out of 114 women, 33 desired a second pregnancy. Out of which 29 had a spontaneous pregnancy. The percentage of total neonatal survival rate after 14 weeks was 92.86% and the percentage of total neonatal survival after 24 weeks was 96.3%. Out of the 29 women with a second pregnancy, 5 women achieved a third pregnancy. The five births occurred after 37 weeks of gestation with a percentage of total neonatal survival of 100%. Conclusion: The cervico isthmic cerclage using the technique of Fernandez makes it possible to obtain subsequent pregnancies without further surgery with very satisfactory results regarding neonatal survival.